Stereotypies in autism: a video demonstration of their clinical variability - Goldman, Sylvie; Greene, Paul E. (Frontiers in Integrative Neuroscience, 2013)
In autism, stereotypies are frequent and disabling, and whether they correspond to a hyperkinetic movement disorder, a homeostatic response aiming at sensory modulation,or a regulator of arousal remains to be established.So far,it has been challenging to distinguish among these different possibilities,not only because of lack of objective and quantitative means to assess stereotypies,but in our opinion also because of the underappreciated diversity of their clinical presentations.Herein, we illustrate the broad spectrum of stereotypies and demonstrate the usefulness of video-assisted clinical observations of children with autism.The clips presented were extracted from play sessions of 129 children with autism disorder.We conclude that compared to widely used questionnaires and interviews,systematic video observations provide a unique means to classify and score precisely the clinical features of stereotypies.We believe this approach will prove useful to both clinicians and researchers as it offers the level of detail from retrievable images necessary to begin to assess effects of age and treatments on stereotypies, and to embark on the type of investigations required to unravel the physiological basis of motor behaviors in autism.